A Study on the Cognition and Emotion Identification of Participative Budgeting Based on Artificial Intelligence - Zhou, Yuan; Zhang, Tianjiao; Zhang, Lan; Xue, Zhaoxin; Bao, Mingxu; Liu, Lingbing (Frontiers in Psychology, 2022)
People's cognition and emotion will affect their behavior. Based on cognition and behavioral theory, this paper studies the role of the individual cognition and emotion between participatory budgeting and organizational performance by adopting the method of questionnaire survey, which aims to seek the mechanism that how cognition and emotion affect the corporate budget performance. It is found that individual cognition and emotion have a positive moderating effect on the relationship between participatory budgeting and organizational performance. The process of cognition and emotion can promote the effect of participatory budgeting on organizational performance. On this basis, according to the theory of artificial intelligence, this paper further designs intelligent identification system of cognition and emotion through the identification of the budget participants characteristics and takes necessary intervention means to improve the budget performance of organization eventually.